Antycykliczny interwencjonizm finansowy państwa włoskiego w latach 1967 -1986 - Kowalczyk, Zygmunt; Przybylska-Kapuścińska, Wiesława (Wydział Prawa i Administracji UAM, 1989)
State countercyclical financial interventionism is conceived here as a permanenet intervention of a state into the economy of a country by means of financial instruments directed at preventing economic fluctuations. In a market economy financial instruments are easier to assimilate than administrative and regulative instruments. The Italian State tries to improve the economic balance of the country by manipulating the financial flows. Thus it prevents business fluctuations of national economy. The possibilities of the State exerting influence on the economy of the country depend on social and economic doctrines adopted by the governing elites and on institutional and administrative infrastructure. In the article the Italian economy has been divided into two basic markets: money and short-term credit market and capital and long-term credit market. The policy of direct refinancing, the regulation of obligatory reserve, the policy of open market and the control of foreign financial relations have been analyzed. The analyses of empirical data justifies the conclusion that financial instruments at the State disposal played small role in moderating the business fluctuations of national economy. Competition among banks, internationalization of bank systems, widening the specialization of banks, the emergence of Euro-currency market are among the most important factors reducing the effectiveness of the State financial policy aimed at preventing business fluctuations of economy. Such a policy is more efficient in times of economic expansion than during depression. The article ends with conclusions concerning the possibilities of employing financial instruments in future, reformed Polish economy.
Antycyclical financial interventionism of Italian state in years 1967-1986